Art in the Land : A Critical Anthology of Environmental Art - Sonfist, Alan; Rosenthal, Mark (New York : E.P. Dutton Inc., 1983)
Haacke, Hans ; Smithson, Robert ; Sonfist, Alan ; Christo ; Holt, Nancy ; etc.
Engels
boek